Discovery of the first genome-wide significant risk loci for attention deficit/hyperactivity disorder. (January 2019) - Demontis, Ditte; Walters, Raymond; Martin, Joanna; Mattheisen, Manuel; Als, Thomas; Agerbo, Esben; Baldursson, Gísli; Belliveau, Rich; Bybjerg-Grauholm, Jonas; Bækvad-Hansen, Marie; Cerrato, Felecia; Chambert, Kimberly; et al.
Abstract Attention deficit/hyperactivity disorder (ADHD) is a highly heritable childhood behavioral disorder affecting 5% of children and 2.5% of adults. Common genetic variants contribute substantially to ADHD susceptibility, but no variants have been robustly associated with ADHD. We report a genome-wide association meta-analysis of 20, 183 individuals diagnosed with ADHD and 35, 191 controls that identifies variants surpassing genome-wide significance in 12 independent loci, finding important new information about the underlying biology of ADHD. Associations are enriched in evolutionarily constrained genomic regions and loss-of-function intolerant genes and around brain-expressed regulatory marks. Analyses of three replication studies: a cohort of individuals diagnosed with ADHD, a self-reported ADHD sample and a meta-analysis of quantitative measures of ADHD symptoms in the population, support these findings while highlighting study-specific differences on genetic overlap with educational attainment. Strong concordance with GWAS of quantitative population measures of ADHD symptoms supports that clinical diagnosis of ADHD is an extreme expression of continuous heritable traits. A genome-wide association study for attention deficit/hyperactivity disorder (ADHD) identifies 12 loci and implicates neurodevelopmental pathways and conserved regions of the genome as being involved in underlying ADHD biology.